STRATEGI MANAJEMEN HUMAS DALAM MENINGKATKAN JUMLAH PESERTA DIDIK MADRASAH DINIYAH - Muhammad Aep Saepudin (STKIP Subang, 2026)
This study was motivated by a researcher's interest in an after-school religious education institution for primary school students. It aims to examine the strategies employed by the institution, particularly regarding the recruitment of new students. Given the crucial role of public relations in such activities, the study seeks to gain deep insight into Public Relations management within this context. A qualitative, descriptive research approach was adopted, involving in-depth interviews with key informants—including the school principal, the committee chairperson, and the foundation chairperson—as well as direct observation of these individuals. The objective was to gain a comprehensive understanding of the institution—which has seen steady growth in student enrollment over the years—and to analyze how the public relations function bridges internal operations with the wider community to foster effective collaboration.